Updates of the role of B-cells in ischemic stroke - Wu, Silin; Tabassum, Sidra; Payne, Cole T.; Hu, Heng; Gusdon, Aaron M.; Choi, Huimahn A.; Ren, Xuefang S. (Frontiers in Cellular Neuroscience, 2024)
Ischemic stroke is a major diseasecausing death and disability in the elderly and is one of the major diseases that seriously threaten human health and cause a great economic burden. In the early stage of ischemic stroke, neuronal structure is destroyed, resulting in death or damage, and the release of a variety of damage-associated pattern molecules induces an increase in neuroglial activation, peripheral immune response, and secretion of inflammatory mediators, which further exacerbates the damage to the blood-brain barrier, exacerbates cerebral edema, and microcirculatory impairment, triggering secondary brain injuries. After the acute phase of stroke, various immune cells initiate a protective effect, which is released step by step and contributes to the repair of neuronal cells through phenotypic changes. In addition, ischemic stroke induces Central Nervous System (CNS) immunosuppression, and the interaction between the two influences the outcome of stroke. Therefore, modulating the immune response of the CNS to reduce the inflammatory response and immune damage during stroke is important for the protection of brain function and long-term recovery after stroke, and modulating the immune function of the CNS is expected to be a novel therapeutic strategy. However, there are fewer studies on B-cells in brain function protection, which may play a dual role in the stroke process, and the understanding of this cell is still incomplete. We review the existing studies on the mechanisms of the role of B-cells, inflammatory response, and immune response in the development of ischemic stroke and provide a reference for the development of adjuvant therapeutic drugs for ischemic stroke targeting inflammatory injury.